2008
DOI: 10.1177/089686080802800605
|View full text |Cite
|
Sign up to set email alerts
|

Claudin Tight Junction Proteins: Novel Aspects in Paracellular Transport

Abstract: Claudins are essential components of the intercellular tight junction and major determinants of paracellular solute fluxes across epithelia and endothelia. Many members of this family display a distinct charge or size specificity, whereas others render the epithelium impermeable to transport. Due to intercellular localization, claudin-mediated transport processes are passive and driven by an electrochemical gradient. In epithelial tissues, claudins exhibit a temporal–spatial expression pattern corresponding wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 51 publications
1
24
0
Order By: Relevance
“…In non‐infected cell layers, claudin 1 and claudin 2 showed a grid pattern marking the cellular walls. These proteins are believed to be present at the apical surface of the cells (66). Infection resulted in a dramatic change in the pattern of adhesion molecules and led to the denaturation of claudin1, claudin 2, and occludin.…”
Section: Discussionmentioning
confidence: 99%
“…In non‐infected cell layers, claudin 1 and claudin 2 showed a grid pattern marking the cellular walls. These proteins are believed to be present at the apical surface of the cells (66). Infection resulted in a dramatic change in the pattern of adhesion molecules and led to the denaturation of claudin1, claudin 2, and occludin.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the transcellular absorption via membrane channels/pumps and intracellular binding proteins referred to above, intestinal calcium is also absorbed through the intercellular space of adjacent cells. This paracellular calcium absorption occurs mainly in the ileum and is regulated by tight junction proteins (claudins 2, 7, and 15) forming cation-selective pores (27,28). Cldn2, Cldn7, and Cldn15 mRNA levels tended to be 2.5 Ϯ 0.8-fold, 2.2 Ϯ 0.6-fold, and 1.5 Ϯ 0.4-fold higher in APOE4 than in APOE3 mice.…”
Section: Vitamin D and Calcium Homeostasis In Apoe Tr Micementioning
confidence: 99%
“…One of the objectives of this study was to determine the viability of Caco-2 cells incubated with known and novel coprocessed non-ionic surfactants at varying concentrations with or without metformin using the MTT assay. Because the transit time of an oral dose of drug through the intestine is 3-4 h (9), the cell viability studies were conducted for 4 h (6,9,11,46). The non-ionic surfactants under consideration in this study (Tables I and II) showed significant differences in the viability of Caco-2 cells incubated at 37°C for 4 h, and their effects were concentration-dependent (Table III).…”
Section: Cell Viability Studies Of Non-ionic Surfactantsmentioning
confidence: 99%
“…Claudin-1, a member of the transmembrane protein family claudin, plays an important role in the maintenance of the polarity, structure, and paracellular transport function of the tight junctions. Alterations in the expression of claudin-1 can decrease the TJ resistance, thereby causing "leakiness" of the TJ and increased paracellular permeability (46). Therefore, Caco-2 cells were exposed to co-processed formulation blends to evaluate the effect of non-ionic surfactants on the expression and localization of claudin-1, which were determined by immunostaining followed by fluorescence microscopy.…”
Section: Effect Of Co-processed Blends Of Non-ionic Surfactants On Thmentioning
confidence: 99%